2006
DOI: 10.1038/nsmb1103
|View full text |Cite
|
Sign up to set email alerts
|

The retromer subunit Vps26 has an arrestin fold and binds Vps35 through its C-terminal domain

Abstract: The mammalian retromer complex consists of SNX1, SNX2, Vps26, Vps29, and Vps35, and retrieves lysosomal enzyme receptors from endosomes to the trans-Golgi network. The structure of human Vps26A at 2.1Å resolution reveals two curvedβ -sandwich domains connected by a polar core and a flexible linker. Vps26 has an unexpected structural relationship to arrestins. The Vps35-binding site on Vps26 maps to a mobile loop spanning residues 235-246, near the tip of the C-terminal domain. The loop is phylogenetically cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
170
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(187 citation statements)
references
References 49 publications
15
170
1
1
Order By: Relevance
“…This is the first demonstration of a role for VPS26 in cargo binding and is consistent with the structural studies of VPS26 that revealed an arrestin-like conformation for the VPS26 protein and predicted a possible cargo-binding activity by analogy with the arrestin family of proteins (Shi et al, 2006;Collins et al, 2008). Although studies in both yeast and mammalian cells have indicated that VPS35 is responsible for the cargo-binding activity of retromer (Nothwehr et al, 2000;Arighi et al, 2004), our data suggest that this is not the case with respect to sorLA binding.…”
Section: Discussionsupporting
confidence: 66%
“…This is the first demonstration of a role for VPS26 in cargo binding and is consistent with the structural studies of VPS26 that revealed an arrestin-like conformation for the VPS26 protein and predicted a possible cargo-binding activity by analogy with the arrestin family of proteins (Shi et al, 2006;Collins et al, 2008). Although studies in both yeast and mammalian cells have indicated that VPS35 is responsible for the cargo-binding activity of retromer (Nothwehr et al, 2000;Arighi et al, 2004), our data suggest that this is not the case with respect to sorLA binding.…”
Section: Discussionsupporting
confidence: 66%
“…Intriguingly the motif in the SorL1/ SorLA cytoplasmic tail is similar to a motif (FYVFSN) present in the yeast Vps10p tail that contributes to the endosome-to-Golgi retrieval of Vps10p (Cereghino et al, 1995), although there is also evidence that additional sequences in Vps10p contribute to interactions with Vps35p (Nothwehr et al, 2000). The recognition of cargo proteins by Vps26 might be expected as its structure was found to be similar to that of b-arrestin -an endocytic adaptor protein that sorts GPCRs into clathrin-coated pits (Shi et al, 2006;Collins et al, 2008). Interestingly, in mammals, Vps26 is present as two paralogues, encoded by the highly related genes Vps26a and Vps26b (Kerr et al, 2005).…”
Section: Cargo Recognitionmentioning
confidence: 98%
“…Arrows indicate punctate compartments, and asterisks point to abnormally enlarged/ vacuolated compartments labeled with VPS35a-GFP. Scale bars, 10 m. Core Retromer Can interact with an Arabidopsis Rab7 Homolog on Endosomal Membranes-Studies relying on the structural analysis of the mammalian VPS subcomplex suggested that the core retromer cannot bind directly to lipids (39,40). Indeed, the sequential action of two Rab GTPases, Rab5 and Rab7, regulates retromer recruitment to membranes in mammalian cells.…”
Section: Vps35 Prlyl Motif and C-end: Conserved Domains With Conservedmentioning
confidence: 99%